Sesamol Induces Apoptosis-Like Cell Death in Leishmania donovani - Ali, Rahat; Tabrez, Shams; Akand, Sajjadul Kadir; Rahman, Fazlur; Husein, Atahar; Arish, Mohd; Alqahtani, Ali S.; Ahmed, Mohammad Z.; Husain, Mohammad; Rub, Abdur (Frontiers in Cellular and Infection Microbiology, 2021)
Background: Visceral leishmaniasis (VL), caused by the protozoan parasite Leishmania donovani (L. donovani) is the most severe form of leishmaniasis. It is largely responsible for significant morbidity and mortality in tropical and subtropical countries. Currently, available therapeutics have lots of limitations including high-cost, adverse side-effects, painful route of administration, less efficacy and resistance. Therefore, it is time to search for cheap and effective antileishmanial agents. In the present work, we evaluated the antileishmanial potential of sesamol against promastigotes as well as intracellular amastigotes. Further, we tried to work-out its mechanism of antileishmanial action on parasites through different assays. Methodology: In vitro and ex vivo antileishmanial assays were performed to evaluate the antileishmanial potential of sesamol on L. donovani. Cytotoxicity was determined by MTT assay on human THP-1 derived macrophages. Sesamol induced morphological and ultrastructural changes were determined by electron microscopy. H2DCFDA staining, JC-1dye staining and MitoSOX red staining were performed for reactive oxygen assay (ROS), mitochondrial membrane potential and mitochondrial superoxide respectively. Annexin V/PI staining for apoptosis, Tunel assay and DNA laddering for studying sesamol-induced DNA fragmentation were performed. Conclusions: Sesamol inhibited the growth and proliferation of L. donovani promastigotes in a dose-dependent manner. It also reduced the intracellular parasite load without causing significant toxicity on host-macrophages. Overall, it showed antileishmanial effects through induction of ROS, mitochondrial dysfunction, DNA fragmentation, cell cycle arrest and apoptosis-like cell death to parasites. Our results suggested the possible use of sesamol for the treatment of leishmaniasis after further in vivo validations.